IMpassion130: Phase III trial comparing 1L atezolizumab with nab-paclitaxel versus placebo with nab-paclitaxel in treatment-naive patients with mTNBC - Emens, Leisha Ann; Schneeweiss, Andreas (Annals of oncology, 2016)
© European Society for Medical Oncology 2016. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved. For permissions, please email: journals.permissionsoup.com.Background: Chemotherapy remains the mainstay therapy for metastatic triple-negative breast cancer (mTNBC) but offers limited clinical benefit at the expense of significant toxicity. This underscores the need for new treatment options. Atezolizumab (atezo) is a mAb specific for PD-L1 that prevents PD-L1 binding to its receptors PD-1 and B7.1, thereby restoring tumor-specific T-cell immunity. TNBC is a rational target indication for atezo due to PD-L1 expression on tumor-infiltrating immune cells (IC), and a high mutation burden that may generate immunogenic neoantigens. Atezo monotherapy was well tolerated and produced durable responses in patients (pts) with mTNBC (Emens et al 2015). Promising activity observed in pts treated with atezo plus nab-paclitaxel (nab-pac) supports the hypothesis that the combination may represent an effective new...
Gesehen am 11.09.2017